Dagestan: Russia's most troublesome republic: political and religious developments on the "Mountain of Tongues" - Halbach, Uwe; Isaeva, Manarsha (2015)
Abstract: Since 2014 the Ukraine conflict has overshadowed Russia's North Caucasus issues, both within the country and abroad. Yet on its Caucasian margins, the Russian state continues to find itself confronted with challenges that affect its internal security and stability as a multi-ethnic state. Dagestan, the largest of the Caucasian republics, has become a flashpoint between security forces and the armed insurgency during the past five years, while changes in Islamist leadership have made it the ideological and logistical centre of North Caucasian jihadism; in this respect it has in fact overtaken Chechnya. What impact did the Chechen wars have on neighbouring Dagestan? How has the religious 'rebirth' since the end of the Soviet Union proceeded in this part of Russia, where Islam is more deeply rooted than anywhere elsewhere in the Federation? How does Dagestan's great ethnic diversity affect its political and social life? This study addresses these questions, exploring the problems that